Evaluating the role of mixed reality in cognitive training of children with ASD: Evidence from a mixed reality aquarium. Issue 162 (June 2022) - Liu, Juan; Bian, Yulong; Xi, Yuting; Zheng, Yawen; Huang, Jin; Gai, Wei; Yang, Chenglei; Meng, Xiangxu
Highlights: The MR training environment can effectively improve the training outcome. The MR training environment benefits the children with ASD from many aspects. The real part of the MR environment may be a double-edged sword. Abstract: Recent studies indicate that Mixed reality (MR) environment showed some advantages in cog- nitive rehabilitation training of children with ASD, but the role of the MR needs to be further explored in the clinical setting. Based on an MR aquarium, we performed two empirical studies to explore the effect of MR in training outcomes of children with ASD in this paper. Study 1 was a one-month longitudinal study, and results showed that the MR aquarium effectively improved the cognitive ability and positive response of children with ASD during training. Interviews with parents and therapists revealed that the MR training environment can effectively attract and maintain the attention of children with ASD, bring better ease of use, multi-sensory feedback, and then assist the rehabilitation training. Study 2 performed a longitudinal comparative study to test the effect of the real part (of MR aquarium) on training performance. Results demonstrated the role of the real part of the MR training environment is a double-edged sword. It can help enhance the interest and performance of children with ASD in the training curriculum, but the positive effect only works in the early period of training.